2021
DOI: 10.3390/agronomy11112244
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Canopy Temperature Using a Random Forest Model to Calculate the Crop Water Stress Index of Chinese Brassica

Abstract: The determination of crop water status has positive effects on the Chinese Brassica industry and irrigation decisions. Drought can decrease the production of Chinese Brassica, whereas over-irrigation can waste water. It is desirable to schedule irrigation when the crop suffers from water stress. In this study, a random forest model was developed using sample data derived from meteorological measurements including air temperature (Ta), relative humidity (RH), wind speed (WS), and photosynthetic active radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…To facilitate an understanding of the relationship between vegetation indices and the chlorophyll content of jujube, a correlation coefficient matrix map is presented in Figure 5. Positive correlations are represented by numbers greater than zero, whereas negative correlations are represented by values less than zero (Yang et al, 2021). The absolute values of the correlation coefficients between SPAD and NDVI, RVI, PhRI, MCARI, TCARI, and GI ranged from 0.64 to 0.82.…”
Section: Correlation Between Spad Value and Vegetation Indices Of Juj...mentioning
confidence: 99%
“…To facilitate an understanding of the relationship between vegetation indices and the chlorophyll content of jujube, a correlation coefficient matrix map is presented in Figure 5. Positive correlations are represented by numbers greater than zero, whereas negative correlations are represented by values less than zero (Yang et al, 2021). The absolute values of the correlation coefficients between SPAD and NDVI, RVI, PhRI, MCARI, TCARI, and GI ranged from 0.64 to 0.82.…”
Section: Correlation Between Spad Value and Vegetation Indices Of Juj...mentioning
confidence: 99%
“…Meanwhile, the UL increased the fit obtained after the DANA. The upper limit could be assumed from the intercept of the NWSB corrected for Ta [ 10 , 44 ] or as the maximum Tc − Ta observed of a known highly stressed canopy [ 45 ]. Moreover, some authors have used a constant as the UL, assuming that the canopy is always above the air temperature when leaf transpiration is suspended, for instance Ta + 4 °C in grapefruit trees [ 46 ] or Ta + 5 °C in olive trees [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Crop water status is associated with various indirect parameters that can be assessed by remote sensing, close observation, and spectral analysis techniques. Studies (Yang et al, 2021) have demonstrated that short-term water deficiency affects the growth process and results in stomatal closure, which ultimately leads to higher leaf temperature. Determining Sc is one of the methods used to quantify stomatal closure, and Sc is a physiological index that is widely used to detect crop water stress.…”
Section: Prediction Model Of Citrus Sc Based On Vegetation Index and ...mentioning
confidence: 99%
“…Currently, sensors are mainly used to measure Sc. Yang et al (Yang et al, 2021) used photosynthetic apparatus to measure the Sc of the Chinese cabbage heart to judge its water stress degree. However, the measurements were time-consuming and laborious and were not widely applicable.…”
Section: Prediction Model Of Citrus Sc Based On Vegetation Index and ...mentioning
confidence: 99%